The Application Value of Early Amplitude-Integrated Electroencephalogram in a Newborn with Nonketotic Hyperglycinemia: A Rare Case Report - Ma, Enting; Li, Wei; Gao, Hong; Ma, Shifeng; Chai, Qianwen; Wei, Li; Wang, Jing (American Journal of Perinatology Reports, 2025)
This study aimed to evaluate the application value of amplitude-integrated electroencephalogram (aEEG) findings in a newborn with nonketotic hyperglycinemia (NKH).The clinical data of a neonatal patient with NKH were retrospectively analyzed. In this study, aEEG was first used to assess brain function in NKH due to AMT gene mutations in the Chinese mainland so far. The aEEG assessment was stratified according to its background pattern, sleep–wake cycle (SWC), and seizure activity, which gave more objective and systemic results.Seizures and burst–suppression pattern were detected on the aEEG. The background belonged to discontinuous voltage, and showed discontinuity of cerebral activity in the form of the burst–suppression pattern. The classification of SWC in this record belonged to the “No SWC” category, which meant the child had severe brain damage. A typical neonatal single seizure was found. The seizure activity lasted approximately 30 seconds. However, clinical symptoms were not observed.Patients with NKH often exhibit complicated clinical phenotypes, and there is a lack of specific symptoms, especially the symptoms of encephalopathy are atypical. aEEG is helpful for the early diagnosis and treatment of seizures. It can help the doctor to carry out appropriate treatment in time. The application value of aEEG in patients with NKH was significant.
Keywords: amplitude-integrated electroencephalogram; nonketotic hyperglycinemia; newborn; burst–suppression